2010
DOI: 10.1002/eqe.986
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic behavior of precast segmental concrete bridge columns with high performance or conventional steel reinforcing bars as energy dissipation bars

Abstract: The cyclic behavior of precast segmental concrete bridge columns with high performance (HP) steel reinforcing bars and that with conventional steel reinforcing bars as energy dissipation (ED) bars were investigated. The HP steel reinforcing bars are characterized by higher strength, greater ductility, and superior corrosion resistance compared with the conventional steel reinforcing bars. Three large-scale columns were tested. One was designed with the HP ED bars and two with the conventional ED bars. The HP E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 181 publications
(74 citation statements)
references
References 6 publications
0
59
0
Order By: Relevance
“…The mild steel deformed bars through segment joints are called energy dissipation (ED) bars to distinguish them from the mild steel reinforcement staying within segments. Relevant studies on the reinforced concrete system can be found in Hieber et al (2005) and Matsumoto et al (2002), studies on the bonded posttensioning system can be found in Arai et al (2006), Shim et al (2008) and Wang et al (2008b), studies on the unbonded posttensioning system can be found in Hewes and Priestley (2002), Billington and Yoon (2004), and Chou and Chen (2006), and studies on the hybrid system can be found in Palermo et al (2007) and Ou et al (2010a).…”
Section: Simplified Analytical Pushover Methods For Precast Segmental mentioning
confidence: 99%
“…The mild steel deformed bars through segment joints are called energy dissipation (ED) bars to distinguish them from the mild steel reinforcement staying within segments. Relevant studies on the reinforced concrete system can be found in Hieber et al (2005) and Matsumoto et al (2002), studies on the bonded posttensioning system can be found in Arai et al (2006), Shim et al (2008) and Wang et al (2008b), studies on the unbonded posttensioning system can be found in Hewes and Priestley (2002), Billington and Yoon (2004), and Chou and Chen (2006), and studies on the hybrid system can be found in Palermo et al (2007) and Ou et al (2010a).…”
Section: Simplified Analytical Pushover Methods For Precast Segmental mentioning
confidence: 99%
“…Several techniques have been developed to improve their seismic performance by increasing their energy dissipation capacity. The most popular approach to increase the energy dissipation capacity of the columns is the use of metallic yielding components at the base of the columns, such as mild steel bars [6,7], high-performance steel bars [8], exterior yielding braces [3,9], and shape memory alloy bars [10,11]. Steel or FRP jackets [12,13], ductile fiber-reinforced concrete [14], and ultra-high performance steel fiber concrete (UFC) segments [15] have also been adopted at the base of the columns, as well as non-metallic devices such as rubber pads [3], elastomeric bearing pads [13,16], and steel shear resistant connecting across segment joints including the base of the column [17].…”
Section: Introductionmentioning
confidence: 99%
“…Mild steel reinforcements are usually disconnected across the joints and transverse reinforcements in segments are expected to control shrinkage and creep. However, precast segmental piers are limited in moderate and high seismicity due to incomprehension on their seismic performance …”
Section: Introductionmentioning
confidence: 99%
“…A hybrid connection incorporating unbonded PT and mild reinforcing steel across segmental joints was conceptually recommended to connect between precast piers and CIP foundation, which was proved to increase self‐centering capacity and ED capacity by cyclic loading tests . Those bars across segmental joints were referred to as ED bars, which were suggested to have a unbonded length and adopt high performance steel reinforcing bars to avoid premature fracture . More ED solutions were proposed for precast segmental piers, such as external mild steel ED device, friction ED caused by sliding of segment joints, external viscous damping device, and so on .…”
Section: Introductionmentioning
confidence: 99%